A rapid review of the use of face mask in preventing the spread of COVID-19. (November 2021) - Abboah-Offei, Mary; Salifu, Yakubu; Adewale, Bisi; Bayuo, Jonathan; Ofosu-Poku, Rasheed; Opare-Lokko, Edwina Beryl Addo
Abstract: Introduction: The original use of face masks was to help protect surgical wounds from staff-generated nasal and oral bacteria. Currently governments across the world have instituted the mandatory use of masks and other face coverings so that face masks now find much broader usage in situations where close contact of people is frequent and inevitable, particularly inside public transport facilities, shopping malls and workplaces in response to the COVID-19. Objective: We conducted a rapid review to investigate the impact face mask use has had in controlling transmission of respiratory viral infections. Method: A rapid review was conducted in line with Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidance. Five electronic databases (CINAHL, Embase, Medline, PsycINFO and Global Health) were searched from database inception to date, using pre-defined search terms. We included all studies of any design and used descriptive analysis to report summary statistics of search results. Data were extracted including sample characteristics, study design, respiratory virus being controlled, type of face masks used and their effectiveness. Results: 58 out of 84 studies met the inclusion criteria, of which 13 were classified as systematic reviews and 45 were quantitative studies (comprising randomised controlled trials, retrospective cohort studies, case control, cross-sectional, surveys, observational and descriptive studies). N = 27 studies were conducted amongst healthcare workers wearing face masks, n = 19 studies among the general population, n = 9 studies among healthcare workers the general population and patients wearing masks, and n = 3 among only patients. Face masks use have shown a great potential for preventing respiratory virus transmission including COVID-19. Conclusion: Regardless of the type, setting, or who wears the face mask, it serves primarily a dual preventive purpose; protecting oneself from getting viral infection and protecting others. Therefore, if everyone wears a face mask in public, it offers a double barrier against COVID-19 transmission.